A class of carbonic anhydrase I – selective activators. (1st January 2017) - Licsandru, Erol; Tanc, Muhammet; Kocsis, Istvan; Barboiu, Mihail; Supuran, Claudiu T.
Abstract: A series of ureido and bis-ureido derivatives were prepared by reacting histamine with alkyl/aryl-isocyanates or di-isocyanates. The obtained derivatives were assayed as activators of the enzyme carbonic anhydrase (CA, EC 4.2.1.1), due to the fact that histamine itself has this biological activity. Although inhibition of CAs has pharmacological applications in the field of antiglaucoma, anticonvulsant, anticancer, and anti-infective agents, activation of these enzymes is not yet properly exploited pharmacologically for cognitive enhancement or Alzheimer's disease treatment, conditions in which a diminished CA activity was reported. The ureido/ bis -ureido histamine derivatives investigated here showed activating effects only against the cytosolic human (h) isoform hCA I, having no effect on the widespread, physiologically dominant isoform hCA II. This is the first report in which CA I-selective activators were identified. Such compounds may constitute interesting tools for better understanding the physiological/pharmacological effects connected to activation of this widespread CA isoform, whose physiological function is not fully understood.